PENGEMBANGAN MODUL CETAK EVALUASI PROGRAM BIMBINGAN DAN KONSELING BAGI GURU BK SMP - Waskitho Asmara Adi; Yari Dwikurnaningsih (UIN Sunan Kalijaga Yogyakarta, 2020)
ABSTRACTThis research was intended to create a product in the form of a printed module evaluating the guidance and counseling program for the junior high school counselors in Salatiga. This research and development study was conducted following the model proposed by Sugiyono, simplified version of the Borg & Gall development research model. The development of the printed module was carried out with the steps: 1) identification of potentials and problems, 2) data collection, 3) product design, 4) design validation, 5) product design revision, 6) product testing, and 7) product revision. The obtained product consists of three parts, namely: 1) the initial section that presents a cover page, preface, table of contents, list of tables and list of images; 2) the content section presents a description of the chapter, indicators of competency achievement, instructions for using the module, material and summary; and 3) the final section presents bibliography, worksheets, competency tests, feedback, follow-up and glossary. Data was collected through documents review and interviews. The data was analyzed using the Miles and Huberman model through data reduction, data presentation and verification. Module validation was done through expert validation, while the product trial was conducted over junior high school counselors. The expert test resulted in a good category with an average score of 4.15. The trial showed an average score of 4.4 with a very good category. The findings suggest that the printed module of guidance and counseling program’s evaluation is feasible and can be implemented by junior high school counselors in Salatiga. Keywords: research and development, printed module, guidance and counseling program’s evaluation ABSTRAKPenelitian ini bertujuan untuk menghasilkan sebuah produk berupa modul cetak evaluasi program bimbingan dan konseling bagi guru BK SMP di Kota Salatiga. Penelitian ini merupakan jenis penelitian dan pengembangan. Langkah-langkah penelitian dan pengembangan menggunakan model yang dikemukakan Sugiyono sebagai penyederhanaan dari model penelitian pengembangan Borg & Gall. Pengembangan modul cetak dilaksanakan dengan langkah-langkah: 1) identifikasi potensi dan masalah, 2) pengumpulan data, 3) desain produk, 4) validasi desain, 5) revisi desain produk, 6) uji coba produk, dan 7) revisi produk. Produk yang dihasilkan terdiri atas tiga bagian yakni: 1) bagian awal yang menyajikan halaman cover, kata pengantar, daftar isi, daftar tabel dan daftar gambar; 2) bagian isi menyajikan deskripsi isi bab, indikator capaian kompetensi, petunjuk penggunaan modul, materi dan rangkuman; serta 3) bagian akhir menyajikan daftar pustaka, lembar kerja, uji kompetensi, umpan balik, tindak lanjut dan glosarium. Metode pengumpulan data dilakukan melalui studi dokumentasi, wawancara dan kuesioner. Teknis analisa data model Miles dan Huberman akan dilakukan dalam beberapa langkah yakni reduksi data, penyajian data dan verifikasi. Validasi modul dilakukan melalui validasi oleh ahli, sedangkan uji coba produk dilakukan kepada guru-guru BK. Hasil uji ahli diperoleh rata-rata skor sebesar 4,15 dengan kategori baik. Hasil uji coba diperoleh skor rata-rata sebesar 4,4 dengan kategori sangat baik. Kesimpulan yang diperoleh adalah modul cetak evaluasi program bimbingan dan konseling layak serta dapat dipergunakan untuk guru BK SMP di Kota Salatiga. Kata Kunci: penelitian dan pengembangan, modul cetak, evaluasi program BK